AB1077 ANTI-IL6-RECEPTOR TOCILIZUMAB IN GRAVES' ORBITOPATHY. MULTICENTER STUDY OF 46 PATIENTS IN CLINICAL PRACTICE. (June 2019) - Atienza-Mateo, Belén; Martín-Varillas, José Luis; Calvo-Río, Vanesa; Demetrio-Pablo, Rosalía; Valls-Pascual, Elia; Valls-Espinosa, Beatriz; Maiz-Alonso, Olga; Blanco, Ana; Torre-Salaberri, Ignacio; Rodriguez-Mendez, Verónica; García-Aparicio, Ángel; González, Raúl Veroz; et al.
Abstract : Background: Graves' orbitopathy (GO) is the most common and important extrathyroidal manifestation of Graves' disease. Corticostereoids and conventional immunosuppressors are not always effective or well tolerated. The IL-6 receptor antibody tocilizumab (TCZ) has demonstrated efficacy in the treatment of this pathology. Objectives: To assess the efficacy of TCZ in refractory thyroid associated orbitopathy (TAO) due to Grave's disease. Methods: Multicenter study of 46 patients with TAO refractory to conventional immunosuppressive therapy. Results: We studied 46 patients (85 eyes) (37 women/9 men); mean age at diagnosis 49.2±11.8 years. Besides oral corticosteroids, before the onset of TCZ patients had been treated with pulses of iv methylprednisolone (42), radioactive iodine (4), methotrexate (2) and other drugs (selenium in 11 cases, methimazole in 8, leflunomide in 1 and azathioprine in 1). 7 patients underwent ocular urgent decompressive surgery. According to the classification of severity of the EUGOGO group (European Group on Graves' Orbitopathy) using the clinical activity score (CAS), before TCZ onset patients whose data were available had severe (27 eyes) or moderate (34 eyes) disease. Moreover, patients presented exophthalmos (53 eyes), strabismus (37 eyes), muscle fibrosis (38 eyes) and dysthyroid optic neuropathy (10 eyes). TCZ was used in monotherapy (43) or combined with methotrexate (2) or azathioprine (1) at 8 mg/kg/iv/4 w (41) or 162 mg/sc/w (5). TCZ yielded rapid and maintained improvement in all ocular parameters as shown in Figures. After a mean of 7.42±6.41 months using TCZ and a mean follow-up of 16.47±11.99 months, all patients experienced ocular improvement, with TCZ withdrawal in 28 cases due to complete remission (10), improvement (12) or stability of ocular inflammation (3), inefficacy (2) and total thyroidectomy (1). Only 5 relevant adverse effects were observed (neutropenia, external otitis, otitis media, costal osteitis and gingival hyperplasia, 1 each). Conclusion: TCZ appears to be a useful and secure option in GO treatment. References: [1] Bartalena L, et al. Consensus statement of the European group on Graves' orbitopathy (EUGOGO) on management of Graves' orbitopathy. Thyroid. 2008; 18 (3:333-346). [2] Russell DJ, et al. Tocilizumab as a steroid sparing agent for the treatment of Graves' orbitopathy. Am J Ophthalmol Case Rep. 2017 Jul 8;7:146-148. Disclosure of Interests: Belén Atienza-Mateo: None declared, José Luis Martín-Varillas: None declared, Vanesa Calvo-Río: None declared, Rosalía Demetrio-Pablo: None declared, Elia Valls-Pascual: None declared, Beatriz Valls-Espinosa: None declared, Olga Maiz-Alonso Speakers bureau: Pfizer, Ana Blanco: None declared, Ignacio Torre-Salaberri: None declared, Verónica Rodriguez-Mendez: None declared, Ángel García-Aparicio: None declared, Raúl Veroz González: None declared, Vega Jovani: None declared, Diana Peiteado: None declared, Margarita Sanchez Orgaz: None declared, Santos Castañeda Consultant for: Amgen, BMS, Pfizer, Lilly, MSD, Roche, Sanofi, UCB, Eva Tomero: None declared, Francisco J. Toyos Sáenz de Miera: None declared, Valvanera Pinillos: None declared, Elena Aurrecoechea: None declared, Ángel Mora: None declared, Arantxa Conesa: None declared, Manuel Fernández: None declared, J. Antonio Troyano: None declared, Iñigo González-Mazón: None declared, Lara Sánchez Bilbao: None declared, D. Prieto-Peña: None declared, Monica Calderón-Goercke: None declared, Miguel Á. González-Gay: None declared, Ricardo Blanco: None declared